Developing the Concept of Forecasting the Economy Need in Qualified Personnel in the Time of Russia’s Passing over to the Digital Model of Development - L. S. Marien; D. M. Melnikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article provides a brief review of causes and principles affecting formation of new approaches to forecasting the Russian economy’s need in qualified personnel in conditions of digitalization. The most important strategic goal of personnel supply to industries in the region is meeting the labour market needs in balanced in quality and quantity staff that would be able to foster the regional economy development and its transfer to the digital model. The authors put forward the enlarged scheme of passing-over to the digital model of development on the basis of the concept of forecasting economy’s need in highly-qualified personnel. Simultaneous use of several approaches and taking into account the system-forming principles could provide an opportunity to estimate the annual extra staff need mainly in the long-term perspective with regard to specification by different types of economic activity and specialization. The authors analyzed the normative-legal base to design the concept and took into account the overseas experience, which could form the foundation for steps aimed at educational sphere regulation and for developing the pool and list of educational programs.